The Inequality of Preschool Enrollment in China： A Narrative Review (Journal of Global Humanities and Social Sciences, 2025)
This narrative review identified and compared previous research information to evaluate the inequality of preschool enrollment. Based on three leading questions, this review identified household registration categories, family income, and parents' education level as sensitive, definite, and solid predictors of preschool enrollment inequality. Moreover, an ecological model covering multilevel analysis will surpass the limitations of past empirical studies that did not uncover the profound structural barriers. Future empirical research needs to test whether 5A1Q are effective indicators to disclose the intricate reasons for inequality in a multilevel model.